Salesperson Empathy and Listening: Impact on Relationship Outcomes - Aggarwal, Praveen; Castleberry, Stephen B.; Ridnour, Rick; Shepherd, C. David (Journal of marketing theory and practice, 2005)
This study fills an important gap in the literature by developing a conceptual model that links salesperson empathy and listening skills to three outcome variables. Responses from a mail survey of 162 buyers from a variety of business organizations were used to test this model using structural equation modeling. The model has an excellent fit (X2 = 1.511, GFI = 0.99, AGFI = 0.94), and indicates a strong positive relationship between empathy and the following: salesperson listening, trust in the salesperson, and satisfaction with the salesperson. Also, listening is positively related to buyer's trust in and satisfaction with the salesperson, but not with future interaction expectations. Trust in and satisfaction with the salesperson were positively related to future interaction expectations.